KONSTRUKSI REALITAS KONFLIK ISRAEL-PALESTINA DI MEDIA ONLINE REPUBLIKA.CO.ID DAN KOMPAS.COM - Mariani Amri (Institut Seni Budaya Indonesia Bandung, 2021)
One of the biggest conflicts that has become the center of attention of the world including Indonesia is the conflict between Israel and Palestine. The conflict between Israel and Palestine is the focus of mass media coverage throughout the world including online media in Indonesia, namely Kompas.com and Republika.co.id. Online media has the ability to construct and to frame reality. But in framing reality each media has a different perspective. This study aims to find out how online media framing of Republika.co.id and Kompas.com against the Palestinian and Israeli conflicts. This study uses a qualitative research method with framing analysis by Robert Entman that focuses on problem identification, causal interpretation, moral evaluation, and treatment recommendation. The findings show that Kompas.com and Republika co.id tend to give moral pretexts by highlighting Palestine and Israel in resolving conflicts through diplomatic relations through international conferences and based on international law. In addition, there is the role of the United Nations and world leaders who take action and respond.